Microbiomes of Thalassia testudinum throughout the Atlantic Ocean, Caribbean Sea, and Gulf of Mexico are influenced by site and region while maintaining a core microbiome - Ugarelli, Kelly; Campbell, Justin E.; Rhoades, O. Kennedy; Munson, Calvin J.; Altieri, Andrew H.; Douglass, James G.; Heck, Kenneth L.; Paul, Valerie J.; Barry, Savanna C.; Christ, Lindsey; Fourqurean, James W.; Frazer, Thomas K.; et al. (Frontiers in Microbiology, 2024)
Plant microbiomes are known to serve several important functions for their host, and it is therefore important to understand their composition as well as the factors that may influence these microbial communities. The microbiome of Thalassia testudinum has only recently been explored, and studies to-date have primarily focused on characterizing the microbiome of plants in a single region.Here, we present the first characterization of the composition of the microbial communities of T. testudinum across a wide geographical range spanning three distinct regions with varying physicochemical conditions. We collected samples of leaves, roots, sediment, and water from six sites throughout the Atlantic Ocean, Caribbean Sea, and the Gulf of Mexico. We then analyzed these samples using 16S rRNA amplicon sequencing. We found that site and region can influence the microbial communities of T. testudinum, while maintaining a plant-associated core microbiome. A comprehensive comparison of available microbial community data from T. testudinum studies determined a core microbiome composed of 14 ASVs that consisted mostly of the family Rhodobacteraceae. The most abundant genera in the microbial communities included organisms with possible plant-beneficial functions, like plant-growth promoting taxa, disease suppressing taxa, and nitrogen fixers.